1984
DOI: 10.1111/j.1469-8137.1984.tb03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Toxicity in Perennial Ryegrass and White Clover

Abstract: Summary Shoot concentrations of Se associated with a 10% reduction in dry matter yield were established for perennial ryegrass (Loliumperenne L.) and white clover (Trifolium repens L.) grown in sand culture. Selenite– treated plants had lower shoot concentrations of Se than those treated with selenate; the critical toxic values associated with a 10% reduction in growth were 48 and 320μg Se g− 1 dry matter shoots for ryegrass plants, and 160 and 330μeg1 dry matter shoots for white clover plants, respectively. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 23 publications
3
43
0
1
Order By: Relevance
“…Assim, alterações na absorção e no teor de S promovidas pelo Se são esperadas, tal como observado por Smith & Watkinson (1984), Banuelos et al (1990), Mikkelsen & Wan (1990) e Barack & Goldman (1997). No presente estudo, o aumento nas concentrações de selenato aumentou o teor de S em todas as cultivares de alface, tendo a maior concentração proporcionado os maiores teores de S (Figura 2a).…”
Section: Resultsunclassified
“…Assim, alterações na absorção e no teor de S promovidas pelo Se são esperadas, tal como observado por Smith & Watkinson (1984), Banuelos et al (1990), Mikkelsen & Wan (1990) e Barack & Goldman (1997). No presente estudo, o aumento nas concentrações de selenato aumentou o teor de S em todas as cultivares de alface, tendo a maior concentração proporcionado os maiores teores de S (Figura 2a).…”
Section: Resultsunclassified
“…It appears, however, that the interaction between sulphate and selenate is more complex than can be explained simply by competitive inhibition for uptake. Smith & Watkinson (1984) and Mikkelsen et al (1988) both observed synergistic effects of selenate on sulphate accumulation, as measured by shoot S content, in monocot and dicot species grown at low sulphate concentrations. The basis of this synergism is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato leaves, the interaction of Se in 0, 0.5, 1, and 2 ppm levels with MO on photosynthetic pigments indicated no significant effect on shoot dry weight and total plant dry weight, however root dry weight significantly reduced (Khavarinejad et al, 2010 Lefsrud et al, 2006;Padmaja et al, 1990;Valkama et al, 2003;Xue et al, 2001). In ryegrass and white clover, by increasing Se concentration chlorophyll content decreased (Smith and Watkinson, 1984). In coffee and corn, different levels of Se in a form of selenite decreased photosynthetic pigments, including chlorophyll, carotenoids and xanthophylls in coffee and chlorophyll formation rate in corn (Jain and Gadre, 1998;Mazzafer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between soil pH and the amount of absorbed Se by plants showed increased soil pH increased Se absorption (Malakooti and Tehrani, 2005). Plants show different physiological reactions to Se levels, some species accumulate it, but some others are sensitive to it and Se is a toxic element to them (Smith and Watkinson, 1984 with Se addition to soils (Hanson et al, 2004;Lyons et al, 2008). Using Se fertilizer under oxidative stress on broccoli reduced (deoxyribonucleic acid) DNA rupturing and breaking (Arvy et al, 1995).…”
Section: Introductionmentioning
confidence: 99%